The Semantic Network of Flood Hydrological Data for Kelantan, Malaysia - Yusoff A.; Md Din N.; Yussof S.; Khan S.U. (Institute of Physics Publishing, 2023)
Disaster prevention; Disasters; Floods; Semantics; Current computing; Data analytics; Disaster management; East coast; Hydrological data; Malaysia; Normal events; Semantic network; Big data; coastal zone; data processing; disaster management; flooding; hazard management; mitigation; Kelantan; Malaysia; West Malaysia